INCREASING STUDENTS’ SPEAKING SKILLS THROUGH ENGLISH SONGS: A CLASSROOM ACTION RESEARCH AT SMAN 1 PAITON - Diana, Siti Nur; Tirmidi, Tirmidi; Samsuddin, Samsuddin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This classroom action research aims to improve the English speaking skills of 11th grade students at SMA Negeri 1 Paiton through the use of English songs as an authentic learning medium. The research was conducted in two cycles using the Kemmis and McTaggart model, which includes the stages of planning, implementation, observation, and reflection. Data were collected through speaking tests, observation sheets, and documentation, then analyzed descriptively, quantitatively, and qualitatively. The results showed a significant improvement in students' speaking skills, as indicated by an increase in the average score from 65.6 on the pre-test to 82.2 on the post-test, as well as an increase in the learning completeness rate from 29.4% to 88.2%. The aspects of fluency, pronunciation, and vocabulary experienced the highest improvement. In addition, students showed greater confidence and more active participation through shadowing and lyric discussion activities. Thus, the use of English songs proved to be an effective learning medium for improving the speaking skills of high school students.Keywords: speaking ability, music literacy, English songs, classroom action research.